2019
DOI: 10.1609/aaai.v33i01.33011401
|View full text |Cite
|
Sign up to set email alerts
|

Deep Reinforcement Learning for Green Security Games with Real-Time Information

Abstract: Green Security Games (GSGs) have been proposed and applied to optimize patrols conducted by law enforcement agencies in green security domains such as combating poaching, illegal logging and overfishing. However, real-time information such as footprints and agents' subsequent actions upon receiving the information, e.g., rangers following the footprints to chase the poacher, have been neglected in previous work. To fill the gap, we first propose a new game model GSG-I which augments GSGs with sequential moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 21 publications
0
42
1
Order By: Relevance
“…Specifically, we found that after a handful of rounds, the quality of learned attacker and defender reached a roughly comparable level with those learned in the same round of the heuristic-driven HADO-EGTA runs. This result contrasts with the experience of Wang et al [46], who found iterative deep RL to be ineffective for their game when starting from random strategies, but successful when seeded with hand-coded heuristics. This disparity could be due to differences in the game setting, the methods, or a combination.…”
Section: Performance With Uninformed Initial Strategiescontrasting
confidence: 91%
See 4 more Smart Citations
“…Specifically, we found that after a handful of rounds, the quality of learned attacker and defender reached a roughly comparable level with those learned in the same round of the heuristic-driven HADO-EGTA runs. This result contrasts with the experience of Wang et al [46], who found iterative deep RL to be ineffective for their game when starting from random strategies, but successful when seeded with hand-coded heuristics. This disparity could be due to differences in the game setting, the methods, or a combination.…”
Section: Performance With Uninformed Initial Strategiescontrasting
confidence: 91%
“…PSRO generalizes what we are terming DO-EGTA primarily by introducing meta-strategy solvers (discussed further below), which support a range of approaches for generating opponents to train against in strategy generation. Recently, Wang et al [46] applied DQN as the oracle for a zero-sum dynamic form of green security game. They found that employing double oracle with DQN may take many rounds and substantial computation to converge, even for modestly sized environments.…”
Section: Double-oracle and Empirical Game-theoretic Methodsmentioning
confidence: 99%
See 3 more Smart Citations